A redescription of Blethisa multipunctata aurata Fischer von Waldheim, 1828 (Coleoptera: Carabidae: Elaphrinae) - Goulet, Henri; Sh., German S. Lafer; Morita, Seiji (Zootaxa, 2009)
Blethisa aurata Fischer von Waldheim, 1828 is redescribed based on recently collected specimens. The taxon is kept as a subspecies of B. multipunctata (Linnaeus 1758). This subspecies is known from forested regions on the Pacific watershed of Russia and Hokkaido (Japan), and Alaska (United States) and subarctic regions of the Northwest Territories (Canada). Blethisa inexspectata Goulet and Smetana, 1983 is a new synonym of B. multipunctata aurata. The remaining North American specimens originally assigned under B. multipunctata aurata (boreal east of Yukon and the Rocky Mountains) belong to B. hudsonica Casey, new status.